TWEAK/Fn14 Signaling Axis Mediates Skeletal Muscle Atrophy and Metabolic Dysfunction - Sato, Shuichi; Ogura, Yuji; Kumar, Ashok (Frontiers in Immunology, 2014)
Tumor necrosis factor (TNF)-like weak inducer of apoptosis (TWEAK) through binding to its receptor fibroblast growth factor inducible 14 (Fn14) has been shown to regulate many cellular responses including proliferation, differentiation, apoptosis, inflammation, and fibrosis under both physiological and pathological conditions. Emerging evidence suggests that TWEAK is also a major muscle wasting cytokine. TWEAK activates nuclear factor-kappa B signaling and proteolytic pathways such as ubiquitin proteasome system, autophagy, and caspases to induce muscle proteolysis in cultured myotubes. Fn14 is dormant or expressed in minimal amounts in normal healthy muscle. However, specific atrophic conditions, such as denervation, immobilization, and starvation stimulate the expression of Fn14 leading to activation of TWEAK/Fn14 signaling and eventually skeletal muscle atrophy. TWEAK also causes slow-to-fast type fiber transition in skeletal muscle. Furthermore, recent studies suggest that TWEAK diminishes mitochondrial content and represses skeletal muscle oxidative phosphorylation capacity. TWEAK mediates these effects through affecting the expression of a number of genes and microRNAs. In this review article, we have discussed the recent advancements towards understanding the role and mechanisms of action of TWEAK/Fn14 signaling in skeletal muscle with particular reference to different models of atrophy and oxidative metabolism.